Assessment of a course of realistic surgical training during medical education as a tool for pre-residential surgical training. Issue 1 (December 2016) - Schoeb, Dominik; Brennecke, Eva; Andert, Anne; Grommes, Jochen; von Trotha, Klaus; Prescher, Andreas; Neumann, Ulf; Binnebösel, Marcel
Abstract Background In recent years the focus on practical skills in the German curriculum of medical school has increased greatly. In this study we evaluate the value of a practical surgery course for medical students as a tool for surgical education, as a way of enhancing interest in surgical fields, and as a method of influencing medical students to subsequently choose a surgical career. Methods The"Feel like a surgeon"- course is an optional practical surgery course in which topographical anatomy and realistic surgical training using fresh human cadavers are combined for medical students of the RWTH Aachen University. Between 2010 and 2015 every student completed a survey before starting and after completing our course, and in 2015 a follow-up was performed. Using a standardized questionnaire, course quality, learning success and impact on post-instructional career and choice of profession was evaluated. Results In total, 82 students attended our course between 2010 and 2015 and took part in the evaluation. Evaluation of the course was positive overall, with an average grade of 1.4° ± °0.50. Significant improvement of basic, as well as more complex surgical skills and theoretical knowledge was noted. Furthermore, self-confidence for patient related assignments improved as well. In the follow-up evaluation, a high level of recommendation for surgical residents was seen, as was a high influence of the course on our students' career choice, although no significant change in career plans before and after taking the course was noted. Conclusions Our results indicate that a practical surgical course can be a valuable tool to prepare students for a surgical residency and to improve their practical skills generally.